Mapping Hispaniola : Third Space in Dominican and Haitian Literature - Myers, Megan Jeanette, 1988- (Book collections on Project MUSE., 2019)
"Mapping Hispaniola considers how certain literary texts offer an alternative to the dominant and, at times, overexaggerated Dominican anti-Haitian ideology and endeavors to reposition Haiti on the literary map of the Dominican Republic and beyond. From the anti-Haitian rhetoric of the intellectual elites of Dominican dictator Rafael Trujillo to the writings of Julia Alvarez, Junot Diaz, and others of the Haitian diaspora, Mapping Hispaniola examines the antipodal portrayal of the two nations of Hispaniola by focusing on representations of the Haitian-Dominican dynamic that veer from the dominant history, disrupting and challenging the 'magnification' and repetition of a Dominican anti-Haitian narrative"--